Proinflammatory Cytokines and Potassium Channels in the Kidney - Kazuyoshi Nakamura; Hikaru Hayashi; Manabu Kubokawa (Hindawi Limited, 2015)
Proinflammatory cytokines affect several cell functions via receptor-mediated processes. In the kidney, functions of transporters and ion channels along the nephron are also affected by some cytokines. Among these, alteration of activity of potassium ion (K+) channels induces changes in transepithelial transport of solutes and water in the kidney, since K+ channels in tubule cells are indispensable for formation of membrane potential which serves as a driving force for the transepithelial transport. Altered K+ channel activity may be involved in renal cell dysfunction during inflammation. Although little information was available regarding the effects of proinflammatory cytokines on renal K+ channels, reports have emerged during the last decade. In human proximal tubule cells, interferon-γ showed a time-dependent biphasic effect on a 40 pS K+ channel, that is, delayed suppression and acute stimulation, and interleukin-1β acutely suppressed the channel activity. Transforming growth factor-β1 activated KCa3.1 K+ channel in immortalized human proximal tubule cells, which would be involved in the pathogenesis of renal fibrosis. This review discusses the effects of proinflammatory cytokines on renal K+ channels and the causal relationship between the cytokine-induced changes in K+ channel activity and renal dysfunction.